Implikasi Pengajian Al-Qur’an Terhadap Perubahan Sikap Masyarakat di Desa Transmigrasi Buket Hagu Aceh Utara - Saputri, Shella; Suri, Sufian; Haq, Vick Ainun; Yunus, Zulia Rahmi Binti (Rumah Jurnal Institut Agama Islam An-Nawawi Purworejo, 2024)
The transmigration community in Buket Hagu Village comes from various tribes and different personalities, especially in internalizing the values of worship, the Qur'an recitation tradition can affect individual and group attitudes, both spiritually and socially. And this is what is felt by the transmigration community in Buket Hagu Village, North Aceh Regency. The purpose of this study is to examine the behavior of transmigration communities in Buket Hagu Village before and after following the Qur'an recitation tradition. This research uses a method with a type of qualitative research, through a field study approach, while the sources in this study are divided into two; namely primary sources by interviewing Ustdaz and Jamaah, while secondary sources refer to data related to research, such as documents: photos, videos, sound recordings and writings. is study expresses and explains that the recitation activities have an influence on the way of dressing the people of Buket Hagu Village which before attending the recitation the way of dressing the people in Buket Hagu Village is still far from Islamic law, the community also recognizes that there are limitations in knowing religious knowledge in depth and the lack of worship and friendship between fellow citizens but after attending the recitation, the community began to improve the way of dressing and felt the increase in religious knowledge and also tried to increase worship and increasingly strengthen the relationship between fellow citizens.